The genus Dolichandrone (Fenzl.) Seem. (Bignoniaceae) in Thailand - Weereesa Boonthasak; CHATCHAI NGERNSAENGSARUAY (Society for Indonesian Biodiversity, 2021)
Abstract. Boonthasak W, Ngernsaengsaruay C. 2021. The genus Dolichandrone (Fenzl.) Seem. (Bignoniaceae) in Thailand. Biodiversitas 22: 1120-1128. Morphological, anatomical, and palynological studies of the genus Dolichandrone (Bignoniaceae) Thailand were conducted. Three species, D. columnaris Santisuk, D. serrulata (Wall. ex DC.) Seem., and D. spathacea (L. f.) Seem. were investigated. Morphological descriptions, distributions and ecological information are provided. A key to the species based on morphological characters are leaflet margins, length of lower cylindric tube and upper campanulate tube of corolla, width of upper campanulate tube of corolla, winged seed, shape and characters of fruits, width of septum, characters and width of pseudoseptum. D. columnaris occurs in low-lying rice fields and marshlands only in the peninsular region. D. serrulata occurs in mixed deciduous forest and low-lying rice fields in the eastern, central and peninsular regions. D. spathacea occurs in edges of mangrove forest in the central, south-eastern and peninsular regions. A key to the species based on anatomical characters includes leaf type, number of rows of palisade cells, arrangement of axial parenchyma, and height of ray parenchyma. All pollen grains are similar and do not provide characters for identification within the genus Dolichandrone.